Guru Penggerak sebagai Agen Perubahan dalam Perspektif Pendidikan Abad 21 - Azzahra Sabrina Hanifa; Rustam Ibrahim (Lembaga Yasin AlSys, 2025)
The Role of Guru Penggerak as Change Agents Is Increasingly Crucial in the 21st Century, One of Which Is Through the Guru Penggerak Program in Indonesia, Designed to Produce Highly Competent Teachers as Well as Leaders of Educational Transformation. This Study Aims to Analyze the Implementation and Impact of the Guru Penggerak Program Using Qualitative Library Research Methods Through Field Study Reviews and Peer-Reviewed Journal Articles. The Findings Indicate That Guru Penggerak Play a Strategic Role in Strengthening Digital Literacy and Integrating Technologies Such as AI, AR, and VR Into Learning, Fostering Professional Learning Communities (PLC) to Enhance Collaboration and Innovation, Internalizing the Profil Pelajar Pancasila to Reinforce Student Character, and Acting as Agents of Social Transformation Through Literacy Movements and Inclusive Education Initiatives. Challenges Identified Include Resistance to Change, Limited Digital Infrastructure in Remote Areas, and Inconsistencies in Policy Support. However, Significant Opportunities Arise From the Merdeka Belajar Policy, Partnerships With the Technology Industry, and Continuous Professional Development Programs. This Study Concludes That Guru Penggerak Constitute a Crucial Pillar of Sustainable Educational Innovation, Which, by Overcoming Barriers and Leveraging Opportunities, Can Shape an Adaptive, Inclusive, and Globally Competitive Education System Aligned With the Demands of the 21st Century.